2019
DOI: 10.3928/1081597x-20190618-01
|View full text |Cite
|
Sign up to set email alerts
|

Visual Outcomes and Patient Satisfaction for Trifocal, Extended Depth of Focus and Monofocal Intraocular Lenses

Abstract: PURPOSE: To assess visual outcomes and patient satisfaction for trifocal and extended depth of focus (EDOF) intraocular lenses (IOLs) compared to monofocal IOLs with and without monovision. METHODS: Consecutive patients underwent bilateral cataract extraction surgery and implantation of either monofocal IOLs, monofocal IOLs using monovision, EDOF IOLs, or trifocal IOLs. Patients with preoperative biometric data, postoperative refraction, and visual acui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
75
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 19 publications
6
75
2
5
Order By: Relevance
“…1,2 The multifocal IOLs, particularly the trifocals, generally provide the highest likelihood of complete spectacle independence. [3][4][5] EDOF lenses are likely to provide good vision at distance and intermediate, with slightly worse near vision, but the expectation is that visual disturbances will be lower with an EDOF IOL because there are not two (or three) distinct foci. 5 This expectation may be in error.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The multifocal IOLs, particularly the trifocals, generally provide the highest likelihood of complete spectacle independence. [3][4][5] EDOF lenses are likely to provide good vision at distance and intermediate, with slightly worse near vision, but the expectation is that visual disturbances will be lower with an EDOF IOL because there are not two (or three) distinct foci. 5 This expectation may be in error.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] EDOF lenses are likely to provide good vision at distance and intermediate, with slightly worse near vision, but the expectation is that visual disturbances will be lower with an EDOF IOL because there are not two (or three) distinct foci. 5 This expectation may be in error. Several studies of the Symfony ® EDOF lens (Johnson & Johnson Vision, Santa Ana, CA) have shown that the visual disturbances experienced by patients are not significantly different than for a trifocal IOL.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these issues, there is a growing interest in new technology that may improve the intermediate performance of monofocal IOLs and minimize the unwanted photic phenomena of multifocality. More than one-third of patients receiving multifocal IOLs reported often experiencing halos or glare [7]. The newly developed monofocal lens, Tecnis Eyhance ICB00 (Johnson & Johnson Vision, Santa Ana, CA, USA) provides reasonable distance vision as well as aspherical lenses with increased power from the periphery to the center and strengthened intermediate vision [3,8].…”
mentioning
confidence: 99%
“… 3 On the other hand, more than a third of patients receive multifocal IOLs experiencing photic phenomena. 4 …”
mentioning
confidence: 99%